HABITAT PEMIJAHANIKAN WADER PARI (Rasbora lateristriata) DI SUNGAI NGRANCAH, KABUPATEN KULON PROGO [Spawning habitat of Rasbora lateristriata in Ngrancah River, Kulon Progo Regency] - Agus Arifin Sentosa; Djumanto Djumanto (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2010)
Yellow rasbora (Rasbora lateristriata) is a riverine fish that has unique spawning behaviour. Observation on its spawning aspects become interesting to carry out. Purpose of this research was to describe spawning site of the fish in Ngran-cah River, Kulon Progo Regency. The study was conducted by survey methods and direct observation in the field. The result showed that yellow rasbora has spawn in shallow riverside with sand and gravel riverbed. Spawning occurred at challenging from wet to dry monsoon with clean and freshly water, enough of oxygen, low water level and low temperature. The characters had been used by fisherman for increasing fish catch ability by make an artificial spawning site modification.